2024
DOI: 10.1111/pcn.13664
|View full text |Cite
|
Sign up to set email alerts
|

The association between levels of brain‐derived neurotrophic factor and comorbid depression in patients with cardiovascular disease: The Framingham Heart Study

Sara Medved,
Joel Salinas,
Daniel Kojis
et al.

Abstract: AimThe current study aims to investigate the association of serum brain‐derived neurotrophic factor (BDNF) levels with symptoms of depression in adults with and without prevalent cardiovascular disease (CVD), an often burdensome comorbidity.MethodsThis cross‐sectional study included participants from FHS (Framingham Heart Study) who had available serum BDNF levels. Depressive symptoms were assessed using the Center for Epidemiological Studies–Depression Scale (CES‐D) with a score ≥16 indicating mild to moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 95 publications
0
0
0
Order By: Relevance
“…The results showed that serum BDNF concentrations were negatively associated with depressive symptoms in patients with CVD, but this association was found only in women. 3 Unfortunately, this study did not elucidate why such a correlation was observed in women and not in men. Future studies should be comprehensive, including platelet function and vascular endothelial cell function, where serum BDNF is most abundantly stored in patients with MD and CVD.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…The results showed that serum BDNF concentrations were negatively associated with depressive symptoms in patients with CVD, but this association was found only in women. 3 Unfortunately, this study did not elucidate why such a correlation was observed in women and not in men. Future studies should be comprehensive, including platelet function and vascular endothelial cell function, where serum BDNF is most abundantly stored in patients with MD and CVD.…”
mentioning
confidence: 79%
“…2 It is known that patients with CVD are more likely to suffer from depression, and serum BDNF levels have been reported to be associated with various diseases including CVD in addition to depression. In this paper, Medved et al 3 demonstrated the association between serum BDNF concentrations and depressive symptoms in patients with and without CVD in the Framingham Heart Study, which included 3716 participants. The results showed that serum BDNF concentrations were negatively associated with depressive symptoms in patients with CVD, but this association was found only in women.…”
mentioning
confidence: 92%